Physiological Adaptations of Mammals of the Arctic Shore. - Folk, G Edgar, Jr; Folk, Mary A (1978)
Contents: Effects of cold exposure on urinary catecholamines in arctic lemmings; Thermogenesis of specific organs in cold acclimated rodents; Induction of summer hibernation by serum from arctic mammals; Spontaneous and induced summer hibernation in 13-lined ground squirrels by marmot and hamster serum; Further evidence for hibernation in bears; The role of adrenoceptors in norephinephrine stimulated VO2 in muscle; Ketamine-HCl anesthesia for the brown lemming; A comparison of body temperatures of least weasels and wolverines; The pineal and photoperiodism in arctic species; Cold acclimatization and the pineal gland of lemmings; Effects of photoperiod, cold acclimation and melatonin; Budget, and Explanation of Budget Items.